A Case Study of a Student’s Reading Habits on Academic Texts - Tiara Utami; Rahayu Apriliaswati; Sumarni Sumarni (Universitas Muhammadiyah Kalimantan Timur, 2022)
This research was aimed to investigate reading habits on academic texts. The investigation was covered reading habits and strategies on academic texts. The participant of this research was an eight-semester student of the English Language Education Study Program who is a good academic achiever, especially in reading subjects. The data were derived from a qualitative case study as the research methodology. Then, the researcher used data triangulation through a semi-structured interview, diaries, and direct observations. All of the data were analyzed by thematic analysis and the investigation answered two research questions such as the research participant’s academic reading habits and academic reading strategies. The first result revealed that; (i) the research participant usually read e-books, journal articles, and educational websites at Untan library, Home, and cafes with approximately 30 mins to 3 hours reading time; several academic reading purposes such as reading for assignments, reading for writing a research proposal, curiosity, self-development, creating ideas, getting knowledge, thinking specifically towards problematic things, recalling memory, spare-time fulfillment, and reading to get motivation; the academic reading factors including self-factor, academic environment factor, peer factor, and the availability of reading sources and access; the second result revealed that; (ii) the student employed four reading strategies namely cognitive strategies that involved self-questioning, note-taking, citing and quoting, outlining, and summarizing; metacognitive strategies, such as evaluating the reading process and realizing; compensation strategies that involved comparing the reading texts, finding the context clues, and reading other sources to improve vocabularies; and mind mapping as the memory strategy in academic reading activity.